2018
DOI: 10.1093/jxb/ery132
|View full text |Cite|
|
Sign up to set email alerts
|

miR156-SPL modules regulate induction of somatic embryogenesis in citrus callus

Abstract: Overexpression of csi-miR156a enhances the somatic embryogenesis capability of citrus through downstream repression of CsSPL3 and CsSPL14.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 91 publications
(126 reference statements)
0
62
0
Order By: Relevance
“…Most of the SPL genes in Arabidopsis are targeted by miR156 and miR157 [14,56,57], and positively regulate downstream flowering genes directly, such as SOC1, LFY, AP1, FUL, and so on [35,51]. This regulation pattern has also been verified in other species [28,53,58,59]. In this study, we found some SPL binding sites (GTAC) in the promoter regions of EjLFY, EjSOC1, and EjAP1 (Sequence S2); and the dual-luciferase reporter assays verified that EjSPLs activate their expression, in which, EjSPL3, EjSPL4, EjSPL5, and EjSPL9 effectively activated EjLFY-1 and EjSOC1-1 expression; and EjSPL4, EjSPL5, and EjSPL9 significantly improve the expression of EjAP1-1 (Figure 7).…”
Section: Discussionmentioning
confidence: 63%
“…Most of the SPL genes in Arabidopsis are targeted by miR156 and miR157 [14,56,57], and positively regulate downstream flowering genes directly, such as SOC1, LFY, AP1, FUL, and so on [35,51]. This regulation pattern has also been verified in other species [28,53,58,59]. In this study, we found some SPL binding sites (GTAC) in the promoter regions of EjLFY, EjSOC1, and EjAP1 (Sequence S2); and the dual-luciferase reporter assays verified that EjSPLs activate their expression, in which, EjSPL3, EjSPL4, EjSPL5, and EjSPL9 effectively activated EjLFY-1 and EjSOC1-1 expression; and EjSPL4, EjSPL5, and EjSPL9 significantly improve the expression of EjAP1-1 (Figure 7).…”
Section: Discussionmentioning
confidence: 63%
“…An example of such regulation was described for micropropagated strawberry, where during in vitro culture, the miR156 is upregulated whereas other miRNAs (miR164, miR172, and miR390) are down-regulated (Li et al 2012). miR156 is one of the eminently conserved plant microR-NAs (Axtell and Bowman 2008) and is involved in many fundamental biological processes that include for example plant phase changes (Massoumi et al 2017;Wu et al 2009), stress response (Matthews et al 2019) or regulating somatic embryogenesis induction (Long et al 2018;Szyrajew et al 2017). Thus, under in vitro conditions, various miRNAs even from the same family, may differ in their expression manner.…”
Section: Epigenetic Aspects Of Plant Regeneration Via In Vitro Tissuementioning
confidence: 99%
“…Callus tissues have an advantage of vigorous growth and can be easily collected without season and space limitation. Callus transformation system has been proven to be a rapid and efficient approach to assess gene function in fruit trees such as apple [46][47][48][49] and citrus 50 . In peach, callus tissues induced from various explants such as leaf, stem and calyx have been reported, but there is no report on establishment of callus transformation system.…”
Section: Discussionmentioning
confidence: 99%